Pengaruh Dimensi Kebiasaan Belajar Terhadap Hasil Belajar Siswa Dalam Pembelajaran Daring Di Sekolah Menengah Atas Negeri 1 Muaro Jambi - Heryadi (Jurnal Pendidikan Islam, 2022)
Distance Learning (PJJ), both online and offline is limited. Evaluation of the Ministry of Education and Culture (Kemendikbud) stated that there was a decline in student learning outcomes. The condition of students and teachers who cannot meet face-to-face because COVID-19 forces us to enforce social distancing and physical distancing has an impact on the learning outcomes of some students.This study aims to determine how much study habits and the value of learning outcomes exist in class X1 students at SMAN 1 Muaro Jambi as a result of PJJ. This study uses a quantitative approach by using the type of data in the form of expost facto. The technique of collecting data is by using questionnaires and documentation. The technique of determining the sample is by using intrapolation calculations based on the category of 75 students. The data collection uses a study habits questionnaire and documentation of students' semester scores. Test the validity of the item analysis using the Pearson product-momentcorrelation coefficient formula in the SPSS v.22 program. Instrument reliability with Cronbach Alpha formula. The prerequisite tests for analysis are normality and linearity tests.The results showed that students' study habits were included in the high category with a percentage value of 75.83%. and for the value of learning outcomes of 80.5 which is in the qualification of grade A (very satisfactory). Hypothesis testing obtained results rhit 0.292 and Sig. 0.001<0.05. The result of the significance value is 0.043 which is smaller than 0.05 (0.043 < 0.05) and the tcount value is 2.060 which is greater than t table 0.2242 (2.060 > 0.2242). From this value it can be concluded that Ha is accepted and Ho is rejected, which means that there is an influence on the variable study habits (X) on student learning outcomes (Y). And for the value of t count is in the positive area. This shows that there is a positive and significant relationship between study habits and learning outcomes. Thus, the higher the student's study habits, the higher the learning outcomes.